Intervensi Metode Kangaroo Mother Care (KMC) Pada Bayi Berat Lahir Rendah: A Literature Review: Literature Review - Paramita Ratna Gayatri; Margaretta, Sheylla (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
Abstract Babies with low birth weight have a number of clinical manifestations both in their physical and psychological conditions. Clinical manifestations that occur are nutritional problems, hypothermia, decreased physiological conditions and cause stress to the mother and baby. Many studies have examined the effectiveness of the Kangoroo Mother Care (KMC) method applied to infants and mothers by looking at its effect on these manifestations. The purpose of this study was to analyze the effectiveness of research on the application of Kangoroo Mother Care (KMC) to mothers and babies. This research method is by reviewing journals collected from several databases such as Google Scholar, PubMab, PMC and Science Direct. The keywords used are Kangoroo” and “preterm” and “infact” and “premature” in the original research article. The reviewed articles were published in the 2015-2022 range. Results: Analysis of 9 journals concluded that the implementation of Kangoroo Mother Care (KMC) had an effect on overcoming increased body weight, increased body temperature, physiological stability and reduced stress for mothers and babies. So that it can be concluded that the implementation of care using Kangoroo Mother Care (KMC) is effectively applied to low birth weight babies and has become a nursing care program for newborns around the world. Keywords: Kangoroo Mother Care (KMC), low birth weight babies